2024
DOI: 10.1182/blood.2023021752
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories and cooperating genomic events define molecular subtypes of BCR::ABL1-positive ALL

Lorenz Bastian,
Thomas Beder,
Malwine J. Barz
et al.

Abstract: Distinct diagnostic entities within BCR::ABL1-positive ALL are currently defined (ICC): 'lymphoid-only', with BCR::ABL1 observed exclusively in lymphatic precursors versus 'multilineage', where BCR::ABL1 is also present in other hematopoietic lineages. Here, we analyzed transcriptomes of n=327 BCR::ABL1-positive ALL patients (age: 2 years - 84 years, median: 46) and identified two main gene expression clusters reproducible across four independent patient cohorts. FISH analysis of FACS-sorted hematopoietic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…5 Previous studies have identified developmental heterogeneity across ALL, 6,7 as well as in Ph+ ALL specifically. 8,9 This developmental heterogeneity has also been linked to treatment response for multiple classes of inhibitors. 6,7,10 Recent work specifically in Ph+ ALL examined developmental subtypes that align with earlier (Early-Pro) and later developmental (Late-Pro) B cell features, finding that the former was associated with poor overall survival upon treatment with the first-generation TKI imatinib.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Previous studies have identified developmental heterogeneity across ALL, 6,7 as well as in Ph+ ALL specifically. 8,9 This developmental heterogeneity has also been linked to treatment response for multiple classes of inhibitors. 6,7,10 Recent work specifically in Ph+ ALL examined developmental subtypes that align with earlier (Early-Pro) and later developmental (Late-Pro) B cell features, finding that the former was associated with poor overall survival upon treatment with the first-generation TKI imatinib.…”
Section: Introductionmentioning
confidence: 99%
“…8 Commitment to earlier or later stages of development has been associated with cooperating alterations in lineage-defining transcription factors ( EBF1 deletion or deletions in IKZF1, PAX5, and CDKN2A, respectively), suggesting that developmental state adherence – and its associated therapeutic response – may be mutationally driven and static upon leukemic transformation. 8,9 However, other studies have nominated the potential for a leukemia’s dominant developmental states to shift in response to therapeutic pressure. Illustratively, non-mutational mechanisms of chemotherapy resistance have been observed in ALL patient-derived xenografts (PDXs), whereby leukemia cells transiently adopt a dormant, stem-like state at MRD; 11 others have demonstrated post-treatment shifts in the abundance of dormant subpopulations mimicking earlier developmental stages.…”
Section: Introductionmentioning
confidence: 99%